The flexural mechanical properties and mesoscopic mechanisms of fracture failure of HPC with ASR inhibition measures under prolonged alkaline solution immersion - Guo, Juan; Liu, Weifeng; Guo, Jianbo; Yu, Hongfa; Ma, Haiyan; Yan, Jun; Tao, Qinghua; Gao, Weiquan; Zhang, Meng; Wang, Fang (Frontiers in Materials, 2024)
The harsh geological conditions in the northwest region of China, characterized by widespread saline-alkali soil rich in alkali ions, pose a high risk of Alkali-Silica reaction (ASR) in concrete, particularly due to the presence of ASR-active natural river sands. To address ASR hazards, locally applied concrete often employs High-Performance concrete (HPC) prepared with high proportions of mineral admixtures. In this paper, the alkali content is controlled by adding mixed water with NaOH to the initial configuration of concrete, and three different alkali content states are set up. A 1 mol/L NaOH solution was used to simulate alkaline conditions, and HPC specimens were immersed for an extended period to investigate the effects of equivalent alkali content, immersion time, concrete strength, and admixture on the flexural mechanical properties of HPC under the condition of long-term alkali immersion. Results indicate that, the strength grade was positively correlated with the flexural strength of HPC, but the alkali content was negatively. Initial immersion significantly enhances strength, followed by a gradual decline after long-term immersion. Among three types of admixture addition methods, the impact on flexural strength of HPC immersed in alkaline solution for ten years follows the order: Double doped air entraining agent and rust inhibitor is greater than single doped air entraining agent is greater than single doped rust inhibitor. In the process of macroscopic test, it is difficult to observe the variation rule of stress and strain in detail, only the final aggregate failure mode can be analyzed. In order to analyze the strain change of the specimen and the failure process of the aggregates more accurately, a three-dimensional random aggregate concrete mesoscopic model was established, and equations relating microhardness to the mechanical properties of concrete components were derived from statistical analysis, providing a basis for parameter selection in the model. Results demonstrate that with increasing strength, the occurrence time of initial cracks is delayed, and the ratio of cracks bypassing aggregates (cracks develop along the ITZ between aggregate and mortar until complete failure) decreases, and the ratio of cracks penetrating aggregates (cracks develop directly through aggregates in an almost vertical direction) increases.